Residual SYNTAX score following coronary artery bypass grafting†. (15th December 2016) - Melina, Giovanni; Angeloni, Emiliano; Refice, Simone; Benegiamo, Cristian; Lechiancole, Andrea; Matteucci, Maria; Roscitano, Antonino; Bianchini, Roberto; Capuano, Fabio; Comito, Cosimo; Spitaleri, Pietro; Tonelli, Euclide; et al.
Abstract: OBJECTIVES: To quantify residual coronary artery disease measured using the SYNTAX score (SS) and its relation to outcomes after coronary artery bypass grafting (CABG). METHODS: We conducted a retrospective analysis on a consecutive series of 1608 patients [mean age 68 years, standard deviation (SD): 7, F:M, 242:1366] undergoing first-time isolated CABG from 2004 to 2015. The baseline SS was retrospectively determined from preoperative angiograms, and the residual SS (rSS) was measured during assessment of the actual operative report for each patient after CABG. Patients were then stratified according to tercile cut points of low (rSSlow 0–11, N  = 537), intermediate (rSSmid  >11–18.5, N  = 539) and high residual SS (rSShigh  >18.5, N  = 532). The Cox regression model was used to investigate the impact of rSS on major adverse cardiac and cerebrovascular events (MACCE) at 1 year. RESULTS: The mean preoperative SS was 26.6 (SD: 9.4) (range 10.1–53), and the residual SS after CABG was 15.3 (SD: 8.4) (range 0–34) ( P  <   0.001 versus preoperative). At 1 year, cumulative incidence of MACCE in the low rSS was 1.5% ( N  = 8/537), 4.5% ( N  = 24/539) in the intermediate and 8.8% ( N  = 47/532) in the high rSS group. Kaplan–Meier analysis showed a statistically significant difference of MACCE-free survival between the three groups (log-rank test, P  <   0.001). The estimated MACCE-free survival rate at 1 year was 98.1% [standard error (SE): 1.6] for the rSSlow, 95.5% (SE: 1.9) for the rSSmid, and 90.5% (SE: 1.3) for the rSShigh group, respectively. After multivariable adjustment, the rSShigh group was independently associated with a higher incidence of MACCE at 1 year (hazard ratio 1.92, 95% confidence interval 1.21–3.23) compared to the rSSlow group. CONCLUSIONS: These unanticipated findings suggest that a residual SS may be a useful tool for risk stratification of patients undergoing isolated first-time CABG. Our study may set the stage for further investigations addressing this important clinical question.